Reliability generalization Meta-Analysis and psychometric review of the Gaming Disorder test (GDT): Evaluating internal consistency - Haitham Jahrami; Waqar Husain; Chung-Ying Lin; Gunilla Björling; Marc N Potenza; Amir Pakpour (Addictive Behaviors Reports)
Gaming disorder (GD) is a growing public health issue requiring reliable screening and diagnostic tools. A commonly used tool for assessing GD is the Gaming Disorder Test (GDT). The GDT assesses GD based on International Classification of Diseases 11th Revision (ICD-11) criteria; however, its psychometric testing has been conducted across studies but yet snythesized. This meta-analysis aimed to synthesize psychometric data regarding the GDT globally. Adhering to pre-registration, a comprehensive search across databases identified 17 eligible studies (n=22,000) in 14 languages reporting on the psychometric properties of the GDT, especially its Cronbach’s alpha. The pooled Cronbach’s alpha was 0.86 (95% CI: 0.83-0.89), indicating excellent internal consistency. Although significant heterogeneity was observed (I2= 98.54%), prediction intervals suggested true outcomes likely shared a positive direction. No moderating effects were found regarding sample characteristics, study quality, or geographical location. The meta-analysis provides robust and quantitative evidence supporting the internal consistency of the GDT across diverse populations. Moreover, qualitative synthesis indicates that the GDT has strong psychometric properties without risk of bias across the analyzed studies, indicating the GDT’s ability to assess GD globally. However, the heterogeneity suggests cautious interpretation of the reliability estimates